Healthful Nutrition of Foods in Navajo Nation Stores: Availability and Pricing. Issue 7 (September 2016) - Kumar, Gayathri; Jim-Martin, Sonlatsa; Piltch, Emily; Onufrak, Stephen; McNeil, Carrie; Adams, Laura; Williams, Nancy; Blanck, Heidi M.; Curley, Larry
Purpose: Low availability and affordability of healthier foods in food stores on the Navajo Nation (NN) may be a community-level risk factor for the high prevalence of obesity among the Navajo people. This study assessed the availability and pricing of foods and beverages in supermarkets and convenience stores throughout the NN. Design: Descriptive study design using the Nutrition Environment Measurement Survey in Stores audit tool. Setting: Supermarkets (n = 13) and convenience stores (n = 50) on NN and border-town supermarkets (n = 9). Subjects: Not applicable. Measures: Availability and pricing of healthy and less-healthy foods. Analysis: Descriptive and χ 2 analyses. Results: Navajo convenience stores offered fewer healthier food options compared to Navajo supermarkets. In Navajo convenience stores, 100% whole grain products, reduced-fat cheese, lean meats, reduced-fat chips, and fat-free or light hot dogs were available in fewer stores than their corresponding less-healthy versions (all with p < .05). In both Navajo supermarkets and convenience stores, 100% whole wheat bread, lean cold cuts, and reduced-fat cheese were all more expensive per unit than their corresponding less-healthy versions (all with p < .05). Conclusions: According to this study, healthier foods are not as readily available in Navajo convenience stores as they are in Navajo supermarkets. Improving access to and affordability of healthier foods in reservation stores of all sizes may support healthy eating among Navajo residents.